Investigating the Relationships Between Cultural Embeddedness, Happiness, and Knowledge Management Practices in an Inter-Organizational Virtual Team - Chumg, Hao-Fan; Huang, Chao-Jung (Frontiers in Psychology, 2021)
This research seeks to develop a better comprehension of the impacts of traditional Chinese cultural elements on knowledge management (KM) practices within contemporary Taiwanese society. To this end, the research draws on the concepts of “guanxi” based on the embeddedness theory concept through the lens of employees’ happiness. A qualitative case study was conducted within a virtual team (in this case, Taiwanese Farmers’ Associations (FAs)) and data were collected from both observations and 36 in-depth, semi-structured interviews. Based on the resulting analysis, the findings show that individuals’ knowledge-sharing behaviour results from a complex interplay of a sense of well-being, guanxi and the Chinese culture rooted within such organisations. The study provides a significant insight into the cultural implications of KM strategies and offers valuable advice for knowledge managers within the context of Chinese society.